ANALISIS SISTEM ADMINISTRASI PERPAJAKAN MODERN TERHADAP EFEKTIVITAS PELAKSANAAN PEMERIKSAAN FUNGSIONAL DAN IMPLIKASINYA PADA KEPATUHAN WAJIB PAJAK: (Studi Kasus pada KPP Pratama Bireuen) - Razif, Razif; Rahmawati, Rahmawati (Jurnal Akuntansi dan Keuangan, 2017)
This study aimed to determine the analysis of the modern tax administration system on the effectiveness of the implementation of functional examinations and their implications for taxpayer compliance at KPP Pratama Bireun. The data used in this study came from direct interviews. The population in this study amounted to 5 functional positions. The analytical method used was descriptive qualitative. The results indicated that the modern tax administration system at KPP Pratama Bireun was in good classification, and also the preparation of inspection programs capable in reducing difficulties on the implementation of tax audits.